Removal of Foreign Body (Denture) in Esophagus with Rigid Esophagoscope - Fachzi Fitri; Hidayatul Fitria (Jurnal Kesehatan Andalas, 2012)
AbstrakLatar Belakang: Seiring dengan meningkatnya pemakaian gigi palsu, kasus tertelan gigi palsu jugameningkat. Gigi palsu yang tertelan harus segera dikeluarkan, karena bila terlambat akan meningkatkan risikoterjadinya komplikasi. Tujuan: Laporan kasus ini dimaksudkan untuk menjelaskan gambaran klinik, diagnosis danpenatalaksanaan benda asing gigi palsu di esofagus. Kasus: Seorang laki-laki 31 tahun dengan benda asing gigipalsu di esofagus. Penatalaksanaan: Esofagoskopi kaku dilakukan untuk pengangkatan gigi palsu Kesimpulan:Diagnosis benda asing gigi palsu di esofagus ditegakkan berdasarkan anamnesis, pemeriksaan fisik, pemeriksaanradiologis dan pemeriksaan esofagoskopi. Esofagoskopi sering dilakukan dalam pengangkatan benda asing diesofagus.Kata kunci: Benda asing, gigi palsu, esofagoskop kakuAbstractBackground: Increasing in the number of people wearing denture, a proportionate increase in theincidence of esophageal impacted denture. Impacted denture has to be removed soon since the diagnosis hasbeen made, because the delay can increase the complication. Purpose: To describe the clinical finding, diagnostictool and management of foreign body (denture) in esophagus. Case: A 31 years old man with impacted denture inesophagus. Management: Rigid esophagoscopy was performed to remove the denture. Conclusion: Removal ofimpacted denture in esophagus was diagnosed based on anamnesis, physical examination, radiological findingand esophagoscopy. Esophagoscopy is often performed in removal of impacted denture in esophagus.Keywords: Foreign body, denture, rigid esophagoscope